2016
DOI: 10.21676/23897864.1864
|View full text |Cite
|
Sign up to set email alerts
|

Dieta de Pomacea canaliculata (Gastropoda: Ampullariidae) en su hábitat natural basada en análisis de contenidos digestivos e isótopos estables

Abstract: Pomacea canaliculata is native to Rio de la Plata basin, and it is invasive in most of South and Southeast Asia after accidental introduction during unsuccessful attempts to establish commercial aquaculture of this species, and being present, the number one pest of rice crops in the region. Investigations in its native habitat are still needed because fundamental issues of its trophic ecology remain unknown. The aim of this research was to study the diet of P. canaliculata in its natural habitat through gut co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Together, carbon and nitrogen isotope ratios ( 13 C/ 12 C and 15 N/ 14 N ratios, respectively) can provide insights into the trophic relationships and the reconstruction of species diets [31][32][33]. Similar, though less comprehensive, studies have investigated the trophic ecology of apple snails (Ampullariidae; [34]) and the reconstructed food webs from ecosystems they inhabit (Pomacea spp. ; [35]).…”
Section: Introductionmentioning
confidence: 99%
“…Together, carbon and nitrogen isotope ratios ( 13 C/ 12 C and 15 N/ 14 N ratios, respectively) can provide insights into the trophic relationships and the reconstruction of species diets [31][32][33]. Similar, though less comprehensive, studies have investigated the trophic ecology of apple snails (Ampullariidae; [34]) and the reconstructed food webs from ecosystems they inhabit (Pomacea spp. ; [35]).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that dietary diversity (exogenous microbial diversity) and host physiological traits (host filtering) may impact gut microbiota alpha diversity (Reese and Dunn, 2018 ; Santos et al, 2021 ). In our study, we expected the collected invasive snails, recognized as agricultural pests and attributed with a diverse diet (López-van Oosterom et al, 2016 ; Saveanu et al, 2017 ; European Food Safety Authority et al, 2020 ), to exhibit greater gut microbiota diversity compared with the native snails. However, our findings did not align with this expectation.…”
Section: Discussionmentioning
confidence: 92%
“…The Ampullariidae are commonly called apple snails [30], including a well-known invasive species, Pomacea canaliculata. This species is considered a voracious omnivore [31][32][33][34][35]. Surprisingly, where P. canaliculata are naturally distributed [30], they represent major components of freshwater biodiversity, serve as ecosystem engineers, and contribute to nutrient turnover, while serving as prey for other species [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%